2014
DOI: 10.1007/5584_2014_38
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Immunosuppressive Treatment in Children with Aplastic Anemia: Rabbit Antithymocyte Globulin

Abstract: Immunosuppressive therapy is the treatment of choice in children with acquired severe aplastic anemia (AA) and no HLA-matched family donor. The paper presents results of a multicenter study of 63 children with AA treated with rabbit antithymocyte globulin (r-ATG) and cyclosporine A as the first line treatment in the years 1996-2012. Therapeutic effects were evaluated at Days 112, 180, and 360. At Day 112, remission was achieved in 28 out of the 63 patients (44.4 %), complete remission in 10 patients (15.9 %), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…26 Another study included 63 pediatric SAA patients without MSD who were treated with rabbit ATG and CsA as firstline IST. 27 Thirty-four of these patients (64.9%) went into remission, but only 24 (38.0%) went into CR. The 10-year OS and FFS were 67 and 57%.…”
Section: Discussionmentioning
confidence: 96%
“…26 Another study included 63 pediatric SAA patients without MSD who were treated with rabbit ATG and CsA as firstline IST. 27 Thirty-four of these patients (64.9%) went into remission, but only 24 (38.0%) went into CR. The 10-year OS and FFS were 67 and 57%.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the EWOG-SAA-2010 interim analysis showed a lower overall response rate (ORR) to IST in patients treated with rATG compared with hATG (22% vs 42%, P = 0.03) but without differences in OS (88% vs 93%) (76). Similarly, Pawelec et al demonstrated the 3-year OS of 78% and the 10-year survival of 67% for hATG and rATG, respectively (77). However, in a meta-analysis by Hayakawa et al, the ORR was significantly higher for hATG vs rATG (risk ratio [RR], 1.27; 95% CI, 1.05-1.54; P = 0.015) (78).…”
Section: Evaluation Of Pediatric Recommendationsmentioning
confidence: 94%
“…Immunosuppressive therapy, including cyclosporin and antithymocyte globulin is used in patients for whom bone marrow transplantation is not an option, with response rates of 60-80 % (Pawelec et al 2008(Pawelec et al , 2015Chang et al 2010;Deyell et al 2011;Bagby et al 2004). However, supportive care with red blood cell transfusions is also essential in many patients to maintain adequate hemoglobin level (70-80 g/L), particularly since the response to immunosuppressive therapy may be delayed.…”
Section: Introductionmentioning
confidence: 98%